Growth and Survival of Fish Tapah (Wallago leeri)In Recirculation Systems With different Water discharge - Hawa Almaidah; Usman M Tang; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from February to April 2014, for 60 days inPonds trialFisheries Faculty and Marine Sciences, University of RiauPekanbaru.The aims research was to growth and survival of fish tapah Wallago leeriinsecirculation system with diferent water floware as.The Method used wasexperiment with 3 treatments and 3 replications. The treatments were P1 = 0,22liter/detik, P2 = 0,29 liter/detik, P3 = 0,41 liter/detik. The best result was treatmentP3 with absolute growth weights (10,22 g), absolute growth length (4,4 cm), dailygrowth rate (0,31 %) and survival rate 96,6 %.Water quality parameters wererecorded during in the researchsuch as ammonia (NH3) 0,0035-0,035 mg/l,temperature 29-310 C, pH 5-6, dissolved oxygen (DO) 3,80-5,90 mg/l.Keywords : Wallago leeri, water discharge, Growth